If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(x-3)2-(x+1)2=12
We move all terms to the left:
(x-3)2-(x+1)2-(12)=0
We multiply parentheses
2x-2x-6-2-12=0
We add all the numbers together, and all the variables
-20!=0
There is no solution for this equation
| 2(x+2(x-3))=4(2x-3) | | 6=2d+2 | | 1/8x+45=3/4x | | 0.2(x+50)-6=0.4(3x+20 | | –3x–4=14. | | n/15=-4/3 | | -4-4x=-2-3x | | (x+2)(x-2)=14 | | -5+10p=-30 | | x^2-4/x^2-3=0 | | H(x)=x-12÷4 | | 6x(7x+x^2)=6x(7x+x^2) | | 15=-2(2t-11 | | X=x-12÷4 | | 3/4(x-8)=1/2(x+2) | | 7x-8+4x=41 | | 3n+15+4n+39=180 | | x=45/100 | | -7+w=7 | | 2x+3x=-14+2x-8+4 | | 7b-(5b+7)=3 | | 5c+5c=6c | | 2/k+2/1=3 | | (x+12)(x+4)=2 | | |2c+8|=|10c||2c+8|=|10c|. | | 2/k+2/1=3 | | -23x^2-80+23=0 | | 5x-10-3x-2=0 | | 45x-7=54 | | 12x-6+8x=52 | | -6=t-1 | | -7n+10=-38 |